ANALISIS PENGARUH KEWARGANEGARAAN DIGITAL TERHADAP KETERAMPILAN WARGA NEGARA DALAM DI ERA GLOBALISASI - Ibtisam, Muhammad Gilang Bayana (UNTIRTA CIVIC EDUCATION JOURNAL, 2023)
The development of information and communication technology has currently changed the way citizens view interaction and participation in community life. Digital citizenship is one of the concepts that refers to the development of information and communication technology, encompassing various aspects of interaction, information acquisition, and the realization of human rights. In realizing the goals of digital citizenship, skills or competencies possessed by a citizen are certainly required. In this case, citizens not only develop individual character but are also able to act actively, productively, and responsibly in shaping digital interaction spaces as a manifestation of good digital citizens. The purpose of this research is to determine the extent of the influence of digital citizenship on citizens' skills in this era of globalization. This research method uses a quantitative method with a descriptive analysis approach where the research data is presented in the form of statistics, thus providing an explanation related to the findings of phenomena or problem formulation presented in this research. The results of this study describe that there is an influence of digital citizenship on citizen skills, as evidenced by hypothesis testing, and there are 4 (four) indicators in this study with a response rate percentage of respondents ≥ 60% (good or high).